1997
DOI: 10.1038/sj.onc.1201063
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of the human CDC25B tyrosine phosphatase. Possible implications for growth control?

Abstract: CDC25B2, a protein tyrosine phosphatase closely related to the putative CDC25B oncogene, was identi®ed in a Burkitt lymphoma cDNA library. CDC25B2 di ers from CDC25B by a 14 residue insertion and a 41 residue deletion, which are both located in the amino-terminal region of the protein, upstream of the catalytic domain. Examination of the genomic sequence revealed that CDC25B1 (formerly B) and CDC25B2 are splice variants of the same gene. A third variant, CDC25B3, that carries both the 14 and the 41 residue seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 27 publications
4
87
0
Order By: Relevance
“…As shown in Figure 1b, using U2OS cells expressing a HA-tagged version of CDC25B3, the most abundant splice variant (Baldin et al, 1997b), we found by western blot analyses that CDC25B3 levels progressively decreased as cells progressed into and exited from mitosis. To investigate further this variation in a more physiological situation, we examined CDC25B endogenous levels in mitotic HeLa cells by immunofluorescence staining.…”
Section: Cdc25b Levels Vary During Mitosismentioning
confidence: 63%
See 1 more Smart Citation
“…As shown in Figure 1b, using U2OS cells expressing a HA-tagged version of CDC25B3, the most abundant splice variant (Baldin et al, 1997b), we found by western blot analyses that CDC25B3 levels progressively decreased as cells progressed into and exited from mitosis. To investigate further this variation in a more physiological situation, we examined CDC25B endogenous levels in mitotic HeLa cells by immunofluorescence staining.…”
Section: Cdc25b Levels Vary During Mitosismentioning
confidence: 63%
“…To investigate further this variation in a more physiological situation, we examined CDC25B endogenous levels in mitotic HeLa cells by immunofluorescence staining. We used a polyclonal antibody raised against a sequence that is present within the B domain (see Figure 1a), one of the domains that are generated by alternative splicing of the CDC25B mRNA (Baldin et al, 1997b;Forrest et al, 1999). This antibody is able to detect CDC25B1 and -3, but not the CDC25B2 splice variant.…”
Section: Cdc25b Levels Vary During Mitosismentioning
confidence: 99%
“…To determine whether this observation could be extended to other cell types, we invalidated p53 in IMR-90 and MCF-7 cells and found that Cdc25B was upregulated in p53 siRNA-transfected cells (Figure 1c and Supplementary Figure S2). As the expression of Cdc25B is cell cycle regulated, being initiated during S-phase, peaking in G2 and declining in mitosis (Baldin et al, 1997b;Korner et al, 2001), we analysed the cell cycle distribution of the siRNA-transfected cells and found that both scr and p53 siRNA-transfected cells showed similar cell-cycle distribution profile (Figure 1d). Thus, increased Cdc25B expression in p53-depleted cells is a direct effect of p53 and not due to alteration of cell-cycle progression.…”
Section: Resultsmentioning
confidence: 91%
“…P13 Sepharose precipitates were washed three times in lysis bu er without phosphatase inhibitors and once in phosphatase bu er (50 mM Tris-HCl pH 8.0, 50 mM NaCl, 1 mM EDTA, 1 mM DTT). P13 Sepharose precipitates were then incubated or not with 3 mg of recombinant GST-CDC25B1 produced and puri®ed as already described (Baldin et al, 1997), for 1 h at 308C in 50 ml phosphatase bu er with gentle mix every 5 min. The p13 Sepharose precipitates were then washed once in kinase bu er (50 mM Tris HCl pH 7.5, 10 mM MgCl 2 , 1 mM DTT, 100 mM ATP) and assayed for kinase activity in a 30 ml volume of kinase bu er containing 0.5 mg/ml histone H1 (Boehringer) as substrate and 5 mCi of [g-32 P]ATP (NEN), 5 min at 308C.…”
Section: G2 Checkpoint Activated By Cdt V Sert Et Almentioning
confidence: 99%
“…After SDS ± PAGE electrophoresis of the reaction mix, H1 histone bands were excised from the gel and counted in a Packard 16500 TR counter (Cerenkov e ect). Western blot analyses were performed essentially as described (Baldin et al, 1997) using polyclonal antibodies against CDK1 (Santa Cruz).…”
Section: G2 Checkpoint Activated By Cdt V Sert Et Almentioning
confidence: 99%